Perencanaan Kurikulum Pendidikan pada Program Pembiasaan Pagi Pra-KBM di Sekolah Dasar berbasis Islam ( Study Kasus di SD PLUS Darul Ulum Jombang) - Indah Nur Lathifiyah (Jurnal Ilmiah Literasi Indonesia, 2026)
This study aims to describe the curriculum planning of the Islamic-based pre-learning morning habituation program (Pra-KBM) at SD Plus Darul Ulum Jombang and to analyze its implementation in strengthening students' character within the framework of the Merdeka Curriculum. This research employed a qualitative approach using a case study design. Data were collected through in-depth interviews, participant observation, and documentation involving the curriculum coordinator, habituation program coordinator, and teachers. Data were analyzed using the interactive model of Miles, Huberman, and Saldana, consisting of data collection, data condensation, data display, and conclusion drawing. The findings reveal that the curriculum planning for the morning habituation program is systematically designed, integrated with the Merdeka Curriculum, and oriented toward developing students' character, spirituality, literacy culture, environmental awareness, and talents. The program includes flag ceremonies, literacy activities, Duha prayer, Qur'an memorization review (murojaah), istighotsah, collective shalawat, environmental planting activities, and the "Ekspresi" program as a platform for students' talent development. The study indicates that the program represents a best practice in implementing Islamic character education through structured school culture. However, improvements are still needed in developing measurable achievement indicators, data-based evaluation systems, standard operating procedures, technology-supported learning innovations, and stronger collaboration between schools and parents. This study contributes a curriculum planning model for morning habituation programs that may serve as a reference for Islamic elementary schools in developing religious, character-oriented, and holistic learning environments.